Inclusion of ‘Climate Basics’ Course into Ethiopia Undergraduate Program is Critical to Build Climate Resilient Economy and Society - Belay, Berhanu; Terefe, Tadesse; Workneh, Sintayehu; Amha, Yosef; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
▪ The gap analyses on undergraduate curricula revealed that the existing Higher Education Institutes programs remained far behind the expected level of integration of Climate Change Education; ▪ The current educational road map, which has proposed critical courses for the first year of the undergraduate program, failed to include the "Climate Basics" course that could offer these students foundational climate science knowledge and tools needed to analyze climate-related risks while maximizing climate change opportunities; ▪ The inclusion of "Climate Basics" as a stand-alone course plays a critical role in broadening the understanding of undergraduate students on various national and international climate discourses.